Tungsten and molybdenum dinitrogen complexes supported by a pentadentate tetrapodal phosphine ligand: comparative spectroscopic, electrochemical and reactivity studies. Issue 16 (18th March 2022) - Junge, Jannik; Froitzheim, Sven; Engesser, Tobias A.; Krahmer, Jan; Näther, Christian; Le Poul, Nicolas; Tuczek, Felix
Abstract : The tungsten dinitrogen complex [W(N2 )(P Me 2 PP Ph 2 )] is compared to its molybdenum analogue. Detailed (IR-spectro)electrochemical investigations were made. In the presence of SmI2 /H2 O the W complex mediates the conversion of N2 to 2.75 equiv. ammonia. Abstract : The tungsten dinitrogen complex [W(N2 )(P Me 2 PP Ph 2 )] (2 ) (P Me 2 PP Ph 2 = [2-(bis[3-(diphenylphosphino)propyl]-phosphinomethyl)-2-methylpropane-1, 3-diyl]bis(dimethylphosphine)) is synthesized and characterized by X-ray diffraction as well as IR and NMR spectroscopies, showing strong analogies to its molybdenum analogue [Mo(N2 )(P Me 2 PP Ph 2 )] (1 ). Whereas cyclic voltammetry studies indicate very similar redox potentials, detailed electrochemical and IR-spectroelectrochemical investigations reveal characteristic differences between 1 and 2 upon electrochemical oxidation in THF. Protonation of 2 with HBAr F (BAr F = tetrakis(3, 5-bis(trifluoromethyl)-phenyl)borate) leads to the hydrazido(2-) derivative 3 which is spectroscopically characterized as well. In the presence of SmI2 /H2 O slightly overstoichiometric conversion of N2 to ammonia (2.75 equiv.) is observed. Although this is far below the activity of the Mo-complex 1, it renders 2 the first W complex to produce more than 2 equivalents of NH3 from N2 upon addition of protons and reductant.